Palaeohydrological Characteristics of the Amlekhganj Formation in Central Nepal Sub Himalaya (Journal of Nepal Geological Society, 1999)
The palaeohydrological studies of the Middle Member of the Amlekhganj Formation, Nepal Sub Himalaya, are based on the grain size and flow depth for values of the palaeoslope gradient, palaeovelocity, and palaeodischarge. The grain size distribution was measured by using the laser diffraction particle size analyser (SALD 3000S; Shimazu), and the flow depth was estimated from the autogenic fining upward succession. The measured values of the palaeoslope gradient, palaeovelocity, and palaeodischarge were 1.21-1.88x10-6 m/m, 0.67-0.78 m/s, and 103-105 m3/s, respectively. The palaeoslope is comparable to the slopes of such modern Himalayan frontal fans as the Kosi Fan.